Barriers and breakthroughs in implementing higher-order thinking skills (HOTS) during teaching practicum: Experience of English pre-service teachers - Handi Pabriana (EduLite: Journal of English Education, Literature and Culture, 2026)
Global challenges and 21st-century skills drive education to prioritize higher-order thinking skills (HOTS) over rote memorization. Educational reforms, including those in Indonesia, emphasize HOTS; however, their successful implementation depends on teachers' abilities. Pre-service teachers recognize the importance of HOTS but struggle to incorporate them into teaching. This study addresses a vital gap in the existing literature by exploring the experiences of six English language pre-service teachers at an Indonesian university who completed a five-month teaching practicum. Utilizing a narrative inquiry approach, the research sought to elucidate the educational experiences of these pre-service teachers and to offer valuable insights into the effectiveness of the pedagogical models employed. Through in-depth, semi-structured interviews and reflective journals, comprehensive and detailed accounts of personal and professional meaning-making processes were obtained. The findings indicated that the implementation of HOTS involves not only cognitive and technical challenges but also an emotional and identity-formation journey. While lecture notes in university courses help students catalogue theoretical concepts, they often encounter a disconnect between theory and classroom practice, leading to cognitive dissonance as they navigate multiple professional identities. Furthermore, pre-service teachers encountered significant systemic and linguistic constraints, notably students’ limited English vocabulary, strict time constraints, and an exam-oriented educational culture. They had devised strategies to address these challenges, including pedagogical adjustments such as shifting from generic textbook examples to localized, contextualized, and culturally relevant topics, as well as engaging in structured reflection on emotional challenges in collaboration with supportive mentor teachers. The insights gained from this research can inform teacher education programs in planning targeted interventions and methods and may prompt policy revisions aimed at producing graduates equipped with higher-order thinking skills.